The Effect of Payment Using Shopeepay Later on Islamic Consumption Behavior in the Millennial Generation - Arum Teguh Fitriyani; Anton Bawono (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The rapid development of technology and the many marketplaces that have mushroomed in Indonesia have made the millennial generation prefer to carry out activities on one hand. One way is to buy various necessities. One of the platforms that provides various community needs is Shopee. Shopee itself has many features, not only providing clothing and necessities but also providing various postpaid services, PBB, and so on. Shopee provides a payment feature, namely Shopeepay Later, where this feature functions almost the same as credit, but Shopee does not ask for any collateral so this feature helps the millennial generation to shop even if they don't have money. This research will discuss the influence of Shopeepay Later payments on Islamic consumption behavior in the millennial generation. This research is quantitative research using interval data types and primary data sources. From the results of this research, convenience, trust, and lifestyle simultaneously influence consumption behavior in the millennial generation, whereas convenience and trust do not influence Islamic consumption behavior in the millennial generation, while lifestyle variables influence consumption behavior in the millennial generation.